(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The current study was conducted on marshy soils found at Rakh Arth Bemina in Srinagar, J&K,India with the goal of quantifying the effect of rice husk ash and cement on the soil’s dry density, optimum moisture content and shear strength. The tests were performed on the original soil sample first, followed by the same tests on the other three samples with Rice Husk Ash(RHA) contents of 10%, 18%, and 22%, respectively, and each containing 8% Cement(C). When 18 percent RHA was used, the goal of increasing optimum moisture content and decreasing maximum dry density was met. As compared to the original sample, the maximum shear strength got increased by 14.8%. Hence,the optimal RHA content is 18%. As a result, rice husk ash combined with a small amount of cement can be a better stabiliser for marshy soils, preventing failure and increasing strength.